Invisible Mind : Flexible Social Cognition and Dehumanization - Harris, Lasana Tacuma, 1981- (Book collections on Project MUSE., 2017)
An interdisciplinary view of the evolution and consequences of flexible social cognition--the capacity to withhold the inference of mental states to other people.